Risk Factors Associated with the Presence of Viral Diseases in Domestic Poultry in the Southern Region of Rio Grande do Sul, Brazil - Hirschmann, Lourdes Caruccio; Fischer, Geferson; Hübner, Silvia de Oliveira; de Lima, Marcelo; Vargas, Gilberto D'Ávila (Acta Scientiae Veterinariae, 2019)
Background: The introduction of any infectious agent into an industrial or subsistence farm worries agribusiness owners in Brazil because it reduces product quality and increases treatment costs, although most diseases are untreatable, thus causing economic losses with morbidity and mortality. Therefore, an epidemiological survey of viral diseases associated with poultry was developed by performing a detailed description of the risk factors that may be related to existing diseases using domestic poultry sample data recorded in the Regional Diagnostic Laboratory (LRD) of College of Veterinary Medicine of the Federal University of Pelotas (UFPel), Rio Grande do Sul, Brazil, from 2000 to 2016. Materials, Methods & Results: Epidemiological and clinical-pathological data were collected and then compared with disease data by multivariate analysis using statistical EpiInfo version 6.04 and Microsoft Office Excel 2010 software. The frequencies and 95% confidence intervals (CI), association measures (odds ratio=OR and relative risk=RR), Chi-square test, and the results considered significant with a value of P ≤ 0.05 were described. A total of 410 samples of domestic poultry were tested, and the results showed 66 (16.1%) viral diseases. The following conditions were the most commonly found diseases in this study: Marek’s disease (42.4%), Infectious bursal disease (31.8%), Avian leukosis (16.6%), Avian pox (7.5%) and Avian infectious bronchitis (1.5%). In this article we discuss the most frequent viral diseases: Marek’s disease (DM) and Gumboro disease. It was also possible to conclude that birds with Marek's disease presented higher odds of developing nerve, tegumentary and locomotors signs (P ≤ 0.05). As well as, more likely to present tumoriform lesions in the liver, spleen, kidneys and heart P ≤ 0.05, as well as lesions in the proventriculus, muscle lesions and in the sciatic nerve P ≤ 0.05. Laying poultry, backyard poultry production and young poultry constitute risk factors for DM (P ≤ 0.05). The results showed that samples with mycotoxicoses were at higher risk of developing DM (P ≤ 0.05). Poultry from industrial system had a higher risk of developing Gumboro disease (P ≤ 0.05). Besides that, domestic poultry with Gumboro disease were more likely to develop signs of depression, nerve signals, tegumentary changes, bursitis, hepatomegaly, renal lesions and splenomegaly (P ≤ 0.05). Discussion: In this research we can observe the domestic poultry with DM presenting tumoriform lesions in several organs, this finding is common in this disease, because it is one of the most frequent viral diseases of neoplastic characteristic. The results show that young birds are a risk factor for DM. In fact, previous works already affirm young birds as being susceptible to disease in relation to adult birds. In this study, laying hens presented a risk factor for DM, however other authors also observed in cut birds or in both types of production. Industrial poultry are at higher risk for DM, this was also reported by other authors, because the disease is of high contagion and morbidity, industrial birds are under high density which facilitates the contact and dissemination of the virus among sick and susceptible birds. In this study, industrial poultry were a risk factor for Gumboro disease, however, other studies show that there is no difference between types of breeding and can also occur in backyard birds. Young poultry and laying hens are more susceptible, and the clinical signs found in the study are compatible with those described in the literature. Through this research on viral diseases, we conclude that our study may complement the already existing official data, since, in a research conducted in the same period, it did not identify the presence of viral diseases in the Southern of RS, but with our research it was possible to register this disease.